Slow waves during deep sleep support cardiac function - Stephanie Huwiler; Manuel Carro-Domínguez; Fabia Stich; Rossella Sala; Florent Aziri; Anna Trippel; Tabea Ryf; Susanne Markendorf; David Niederseer; Philipp Bohm; Gloria Stoll; Lily Laubscher; et al. (Bern Open Publishing, 2024)
Introduction The role of sleep in cardiovascular health, particularly the impact of deep non-rapid eye movement (NREM) sleep, is gaining interest in the prevention of cardiovascular diseases (Grandner et al., 2016). Essentially slow waves, prominent brain oscillations during deep sleep, seem to represent an important cardiovascular recovery process for the human body. However, to date, the specific mechanisms through which sleep affects cardiovascular function and whether slow waves accelerate recovery remain elusive. Methods Here, we explored the role of slow waves in promoting cardiovascular function. In this randomized, cross-over trial involving 18 healthy male participants (Huwiler et al., 2023), we investigated how experimentally enhancing slow waves via auditory stimulation (Huwiler et al., 2022) impacts cardiovascular dynamics during sleep and next-day cardiac function, assessed via an echocardiography. All participants underwent three experimental nights including two conditions for slow wave enhancement and one SHAM control condition while brain oscillatory, blood pressure, and cardiac dynamics were continuously measured during sleep. Results Using a linear mixed-effect model approach, we found auditory stimulation to significantly increase slow wave activity (F(2, 33.095) = 11.397, p < 0.001) during times of stimulation. This slow wave enhancement coincided with a dynamic cardiovascular activation, indicated through short increases in blood pressure and a biphasic heart rate response. After sleep, we found a significant increase in general longitudinal strain (F(2, 34) = 81.17, p < 0.001), an increase in left-ventricular ejection fraction (F(2, 34) = 4.55, p = 0.018), and a decrease in E/e' ratio (F(2, 34) = 3.38, p = 0.046) for both slow wave stimulation conditions compared to SHAM. Discussion/Conclusion We show that slow wave stimulation induces a cardiovascular activation response possibly related to increasing cardiovascular stability during sleep (De Zambotti et al., 2016). Moreover, we demonstrate that slow wave stimulation enhances left-ventricular systolic and diastolic function, both together indicating improved cardiac function. Altogether, this points towards the functional involvement of slow waves in promoting cardiovascular health. Therefore, sleep slow wave stimulation may be considered a potential supplementary method in treating cardiovascular diseases involving decreased left-ventricular function. Furthermore, our findings hint that enhancing slow waves could potentially optimize post-exercise recovery processes and increase cardiovascular well-being. References De Zambotti, M., Willoughby, A. R., Franzen, P. L., Clark, D. B., Baker, F. C., & Colrain, I. M. (2016). K-complexes: Interaction between the central and autonomic nervous systems during sleep. Sleep, 39(5), 1129-1137. https://doi.org/10.5665/sleep.5770 Grandner, M. A., Alfonso-Miller, P., Fernandez-Mendoza, J., Shetty, S., Shenoy, S., & Combs, D. (2016). Sleep: Important considerations for the prevention of cardiovascular disease. Current Opinion in Cardiology, 31(5), 551-565. https://doi.org/10.1097/HCO.0000000000000324 Huwiler, S., Carro-Domínguez, M., Stich, F. M., Sala, R., Aziri, F., Trippel, A., Ryf, T., Markendorf, S., Niederseer, D., Bohm, P., Stoll, G., Laubscher, L., Thevan, J., Spengler, C. M., Gawinecka, J., Osto, E., Huber, R., Wenderoth, N., Schmied, C., & Lustenberger, C. (2023). Auditory stimulation of sleep slow waves enhances left ventricular function in humans. European Heart Journal, 44(40), 4288-4291. https://doi.org/10.1093/eurheartj/ehad630 Huwiler, S., Carro Dominguez, M., Huwyler, S., Kiener, L., Stich, F. M., Sala, R., Aziri, F., Trippel, A., Schmied, C., Huber, R., Wenderoth, N., & Lustenberger, C. (2022). Effects of auditory sleep modulation approaches on brain oscillatory and cardiovascular dynamics. Sleep, 45(9), 1-36. https://doi.org/10.1093/sleep/zsac155